DISTRIBUTION OF MUNG BEAN CEREAL AS AN EFFORT TO LIVE A HEALTHY LIFE THROUGH BREAKFAST (Jurnal Abdimas Administrasi Kesehatan, 2022)
The purpose of this activity is to provide education to the community about the distribution of mung bean cereal as an effort to live a healthy life through breakfast. Through this socialization about the prevention of malnutrition in the people of Samarinda, it is hoped that they can be aware and understand about healthy living efforts through breakfast. By running breakfast as a routine through mung bean cereal, this step can be an eradication of the problem so as to avoid disease. The distribution of ijo bean porridge as an effort to live a healthy life through breakfast is carried out by distributing mung bean cereal, spreading posters and qr codes